Large-Scale Exfoliation of Inorganic Layered Compounds in Aqueous Surfactant Solutions - COLEMAN, JONATHAN; WANG, JING; KHAN, UMAR; NICOLOSI, VALERIA; DUESBERG, GEORG (My University, 2011)
Thumbnail image of graphical abstract A method to exfoliate MoS2 in large quantities in surfactant-water solutions is described. The layered material tends to be exfoliated as dispersions of thin, relatively defect-free flakes with lateral sizes of hundreds of nanometers. This method can be extended to a range of other layered compounds. The dispersed flakes can be mixed with nanotubes or graphene to greate functional hybrid materials.
PUBLISHED
Keywords: nanosheets; exfoliation; surfactants; batteries